2021
DOI: 10.5005/jp-journals-10071-23803
|View full text |Cite
|
Sign up to set email alerts
|

Use of Handheld Ultrasound Device with Artificial Intelligence for Evaluation of Cardiorespiratory System in COVID-19

Abstract: A bstract Background Coronavirus disease-2019 (COVID-19) causes various cardiopulmonary manifestations. Bedside ultrasound helps in the rapid diagnosis of these manifestations. Vscan Extend™ (GE, Wauwatosa, WI, USA) is a handheld ultrasound device with a dual probe and an artificial intelligence application to detect ejection fraction. It can help in reducing the time for diagnosis, duration, and the number of healthcare workers exposed to COVID-19. This is a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A linear probe acquires more optimal images of the pleural line appearance and subpleural changes whereas a curvilinear probe provides a panoramic view from the pleural line to identify B-lines and consolidations ( 48 , 49 ). Handheld pocket-sized ultrasound devices have been shown to have good agreement with standard POCUS scanners when visualising interstitial patterns, consolidation and calculation of LUS score in ICU patients ( 50 ) as well as patients with COVID-19 ( 51 , 52 ). Therefore, handheld pocket-sized ultrasound devices or wireless transducers may be preferable compared to larger POCUS machines during a pandemic as it is more convenient to sheath with single use plastic covers ( 53 ) and easier to disinfect.…”
Section: Discussionmentioning
confidence: 99%
“…A linear probe acquires more optimal images of the pleural line appearance and subpleural changes whereas a curvilinear probe provides a panoramic view from the pleural line to identify B-lines and consolidations ( 48 , 49 ). Handheld pocket-sized ultrasound devices have been shown to have good agreement with standard POCUS scanners when visualising interstitial patterns, consolidation and calculation of LUS score in ICU patients ( 50 ) as well as patients with COVID-19 ( 51 , 52 ). Therefore, handheld pocket-sized ultrasound devices or wireless transducers may be preferable compared to larger POCUS machines during a pandemic as it is more convenient to sheath with single use plastic covers ( 53 ) and easier to disinfect.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a paper recently appeared, in which five HHUS devices are used for AI-assisted measurement of the optic nerve sheath [ 64 ]. It is to be expected that AI will positively influence both the diagnostic options for the use of HHUS devices and their B-image quality [ 65 , 66 ]. Due to their increasingly acceptable image quality, their compactness, and, not least, their affordable prices, HHUS devices will inevitably be further developed and established within AI-based sonographic diagnostics, and extensively used within telemedical networking.…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care ultrasound (POCUS) has a wide diagnostic application in intensive care, making it easier to use and interpret such imaging modalities as transthoracic and transesophageal echocardiography, lung ultrasound, ultrasound of a patient in shock, and patients with other life-threatening conditions. Due to the complexity of ultrasound assessment in intensive care, the physician’s purpose of using AI in this setting is to help assess the patient’s condition based on US imaging of various systems and organs and assess the patient’s hemodynamic profile [ 4 , 5 , 6 ]. The literature has shown that AI-guided POCUS will most likely increase the efficiency and effectiveness of ultrasound imaging [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of ultrasound assessment in intensive care, the physician’s purpose of using AI in this setting is to help assess the patient’s condition based on US imaging of various systems and organs and assess the patient’s hemodynamic profile [ 4 , 5 , 6 ]. The literature has shown that AI-guided POCUS will most likely increase the efficiency and effectiveness of ultrasound imaging [ 4 , 7 ]. AI-supported point-of-care protocols also have particular educational applications, enabling young medical students to improve ultrasound techniques and increasing the identifiability of anatomical structures, which is necessary to perform procedures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation